2021
DOI: 10.1186/s12974-021-02185-0
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 induces a pro-neurogenic microglial phenotype via PPARγ activation in male mice exposed to chronic mild stress

Abstract: Background Anti-inflammatory approaches are emerging as a new strategy for the treatment of depressive disorders. Ginsenoside Rb1 (GRb1), a major component of Panax ginseng, can inhibit inflammatory cascade and alleviate depressive-like behaviors. Microglia can promote or inhibit adult hippocampal neurogenesis according to their functional phenotypes. Here, we examine whether GRb1 may exert antidepressant effects by promoting a pro-neurogenic phenotype of microglia and thereby increasing neurog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 61 publications
(65 reference statements)
1
31
0
Order By: Relevance
“…In BV2 microglial cells, LPS exposure induced an imbalance between the pro-inflammatory and anti-inflammatory microglial phenotype [ 71 ], activated TLR4/nuclear factor-kappa B (NF-κB) pathway, and downregulated TREM2 expression [ 72 ]. In the HIP and cortex of CMS-exposed mice, immunofluorescence staining revealed that the activated microglia (Iba-1 positive cells), as well as increased pro-inflammatory microglial markers (IL-1β, TNF-ɑ, IL-6, INF-γ, and iNOS) and decreased anti-inflammatory markers (Ym1, IL-4, IL-10, and Arg-1), suggesting a transformation of the microglial phenotype [ 73 ]. The CSDS paradigm also produces mood alterations and microglial activation, as well as ROS elevation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In BV2 microglial cells, LPS exposure induced an imbalance between the pro-inflammatory and anti-inflammatory microglial phenotype [ 71 ], activated TLR4/nuclear factor-kappa B (NF-κB) pathway, and downregulated TREM2 expression [ 72 ]. In the HIP and cortex of CMS-exposed mice, immunofluorescence staining revealed that the activated microglia (Iba-1 positive cells), as well as increased pro-inflammatory microglial markers (IL-1β, TNF-ɑ, IL-6, INF-γ, and iNOS) and decreased anti-inflammatory markers (Ym1, IL-4, IL-10, and Arg-1), suggesting a transformation of the microglial phenotype [ 73 ]. The CSDS paradigm also produces mood alterations and microglial activation, as well as ROS elevation.…”
Section: Introductionmentioning
confidence: 99%
“…Direct and indirect evidence support that some ginsenosides (such as ginsenoside Rg3, Rb1, and Rg1) induce the anti-inflammatory actions of macrophages and microglia [ 195 ]. Ginsenoside Rb1 is a typical 20( S )-protopanaxadiol-type saponin and exerts significant antidepressive effects in chronic stress models [ 73 , 196 , 197 ]. It is known that Rb1 regulates microglial activation, protects neurons from inflammatory and oxidative damage, and promotes neurogenesis [ 198 , 199 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TST was conducted as described previously with slight modifications (Zhang et al 2021a ). In brief, the immobility time of each mouse was recorded for the last 4 min following 2 min habituation during a 6 min test period.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent work showed that Rb1 can significantly ameliorate depressive-like behavior induced by chronic social defeat stress and modulates the BDNF-Trkb signaling pathway ( 27 ). Ginsenoside Rb1 demonstrated substantial antidepressant effects in rats by modulation of amino-acidergic and monoaminergic receptors and their associated neurotransmitters, induced microglial activation, and improved adult hippocampal neurogenesis in mice subjected to chronic mild stress ( 28 ). Unfortunately, very little is known about Rb1's antidepressant-like effect on behavioral impairments caused by CSDS, or on the exact neuronal processes underlying, or about Rb1's significance to the neuroprotective effect of slowing the inflammatory process in depression.…”
Section: Introductionmentioning
confidence: 99%